2000
DOI: 10.1016/s0928-8244(99)00188-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered antigenicity is seen in the lipopolysaccharide profile of non-serotypeable Actinobacillus actinomycetemcomitans strains

Abstract: Non-serotypeable Actinobacillus actinomycetemcomitans strains may be derived from the serotypeable ones. In the present study, we compared the outer membrane proteins (OMPs) and lipopolysaccharides (LPSs) of serotypeable and non-serotypeable A. actinomycetemcomitans strains (n=24) of the same genotype in the same subject (n=6) to find out if alterations on the cell-surface contribute to the non-serotypeability. Serotypeable and non-serotypeable A. actinomycetemcomitans strains showed great similarity in the OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Paju et al (14) reported that both serotypeable and nonserotypeable A. actinomycetemcomitans strains belong to identical AP-PCR genotypes. It is possible that some of these nonserotypeable strains are derived from serotypeable strains (14). Our multiplex PCR test may be useful for identifying the origin of nonserotypeable A. actinomycetemcomitans strains.…”
mentioning
confidence: 99%
“…Paju et al (14) reported that both serotypeable and nonserotypeable A. actinomycetemcomitans strains belong to identical AP-PCR genotypes. It is possible that some of these nonserotypeable strains are derived from serotypeable strains (14). Our multiplex PCR test may be useful for identifying the origin of nonserotypeable A. actinomycetemcomitans strains.…”
mentioning
confidence: 99%
“…The strains were serotypeable or non-serotypeable to lack of serotype Antigen in A. actinomycetemcomitans rEsEArch rEPOrts clinical J Dent Res 89 (3) 2010 Lack of Serotype Antigen Expression 293 serotypes a-e by immunodiffusion assay and were selected from our strain collection to represent various genotypes as determined by arbitrarily primed PCR Dogan et al, 1999;Paju et al, 2000b) (Appendix Table 1). When available, several non-serotypeable strains per individual were included.…”
Section: Materials and Methods Bacterial Strainsmentioning
confidence: 99%
“…LPSs of the A. actinomycetemcomitans strains were isolated as previously described (21). Briefly, the strains were grown on Trypticase soy agar (Difco Laboratories, Detroit, Mich.) plates in 5% CO 2 in air at 37°C for 2 to 3 days.…”
Section: Methodsmentioning
confidence: 99%